(untitled) (Al-Qamar, 2021)
This article aims to highlight the exclusive characteristics of Sīrah writings of Mowlānā Syed Abu al-Ḥassan ʻAlī Nadvī, (1914-1999), an eminent Indian Islamic scholar, focusing his book “Nabī-i-Rahmat”. It finds that Nadvī not only narrates the life aspects of the noble character of the Prophet (ﷺ) but also presented the logical and rational explanation of the sacred life. The book is adorned with all historical and scholarly themes relevant to the Sīrah of the Prophet. The study suggests that the book should be included in the curriculum of educational institutions, colleges, universities and madrassas, and short summaries and pamphlets should be prepared to acquaint students with the themes and message of the book.